PENGARUH BRAND IMAGE TERHADAP LOYALITAS NASABAH DALAM MENGGUNAKAN JASA PERBANKAN PADA PT. BANK SYARIAH MANDIRI CABANG MALANG - Hasan, Irmayanti; Firmansyah, Fani (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2014)
Abstract Brand awareness is the basic dimensions of brand equity. Brand awareness shows two levels of awareness; that is familiar to the brand (brand recognition) and is able to recall the brand (brand recall). Brand image is a type of association that arises in the minds of consumers when considering a particular brand. Brand image (brand image) is one of the components that affect customer loyalty. Competitive companies use brand image to attract consumer attention and loyalty bind. The population in this study is the city of Malang Islamic banking customers. The method of sampling is non-probability sampling technique by purposive sampling. The sampling method aims to obtain samples reprsentatif according to specified criteria. The results of this study are variable brand image consisting of image bank, the customer's image, the image of banking products, simultaneously have a significant effect on customer loyalty in the use of banking services and banking product image variable partial effect. This indicates that the majority of customers choose PT. Bank Syariah Mandiri Branch Malang because the image of banking products from PT. Bank Syariah Mandiri Branch Malang.